Incidence in the Transition from Presential Education to Distance Education Through Technological Tools in the Learning of English Speaking in the Academic Training General English Program of the Technological Center of Cúcuta Students (Docentes 2.0 Journal, 2020)
With the presence of a new virus (COVID-19), humanity has had the obligation of a technological movility in order to continue with its daily routine. In that way, education has done an inmediate adaptation according to knowledge transfer method. Nowaday, electronic devices are a necessity in every house for those who believe in transformation, no matter what the escenary is. This paper job, is to expose the principal discovery about how the transition to distance education through technological tools has impacted on the academic English program of the CTC students, not only about social aspects but also on studies levels. Using the exploration, analysis and comparison technique, it could be seen how students, teachers and administrative personal are aware about the currently situation and the way they have been adapted into this. In the same way, it is demonstrated that the methodology and pedagogical aspects applied by every teacher of the program inside the new educational system (distance learning) in order to develop the English language skills in the registered individuals, have shown that this process was accepted by the half (50%) of population (according to the first cohort registration) but there is a gradual increase on the following cohorts in which technological tools have been applied, and as a conclusion, as long time goes by and is demanding the new way of studying, the impact among the apprentices tends to be satisfactory.
Keywords: Transition; impact; distance learning; technological tools; bilingualism